The Church’s Prayer on Deathbed and the Moral Reflection on Euthanasia - Vantsos, Miltiadis (Conatus - Journal of Philosophy, 2018)
Associating a prayer that belongs to the long-standing tradition of the Orthodox Church with a contemporary theme, such as euthanasia, may seem strange, as at the time the prayer was written, the ethical consideration of euthanasia was certainly unknown. However, the timelessness of illness, pain and death, the existential agony of human at the end of life and the unwavering commitment of the Church to the suffering and dying person allow, in our view, the exploration of the Church’s prayer on deathbed in the context of the good and desirable death. It is noteworthy that, while in all liturgical texts the cure from illness is pleaded for, in this specific prayer the desire of death is expressed, in order to redeem human from the “unbearable suffering due to the bitter illness”. In this perspective the content of the prayer is presented, which seems to have important elements in common with the modern demand for a positive response to euthanasia, namely the free will of the patient and the desire for a quick and painless death. Despite these, the prayer on deathbed does not favor the acceptance of euthanasia for two reasons: Firstly, the request for a painless death is addressed to God and its fulfillment is expected only from Him and not from the doctor or the relatives. And second, this request is accompanied by a plea for the forgiveness of the sins of the moribund, expressing his faith and hope in eternal life, his trust in God and not despair and distress. The article is concluded with some remarks concerning the understanding of good death from the point of view of orthodox ethics.